DEVELOPMENT COMPUTATIONAL THINKING GAMIFICATIONS LEARNING PLATFORM - Pramudhita, Agung Nugroho; Nurhasan, Usman; Triswidrananta, Odhitya Desta; Lisuardi, Dina (Pascasarjana Universitas Negeri Malang (UM), 2022)
Students frequently encounter difficulties in describing complex problems as simple ones, analyzing the general differences and similarities of a problem, and generalizing problem solving patterns based on computational thinking. One solution to these issues is to use the concept of gamification on the learning platform. Which aims to develop a computational thinking learning gamification website. The gamification website developed applies gamification elements in CT learning such as implementing points where each level of difficulty level has a different point. Implements 3 levels namely “siaga”, “penegak”, and “penggalang” by applying the level the user can find out the level of difficulty of the questions according to the level provided such as. Then when working on the questions, you will get a badge that aims to symbolize the extent of the user's ability level when finished working on the questions. And the last one implements a Leaderboard which displays the user's overall rating. Users find the website for Computational Thinking Gamification to be satisfying as well as functional, according to the average score of 87 percent that it received from twenty different participants.